1985
DOI: 10.1007/bf00118198
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sister chromatid exchanges in lymphocytes cultured from 71 healthy men

Abstract: Sister chromatid exchanges (SCE) were analyzed in peripheral blood lymphocytes from a select group of 71 healthy men, 56 nonsmokers and 15 cigarette smokers. In addition to estimating baseline SCE, data were examined to seek relationships of SCE frequencies to age and smoking. The baseline value of 7.53 SCE per cell from the 56 nonsmokers was within the range (5.60 to 9.10 SCE/cell) reported for other human populations. No relationship was found between the mean SCE frequency per cell and age. However, a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…Age significantly affects the incidence of SCE. Older animals develop more SCEs per cell compared with younger animals (Sinha et al 1985;Lazutka et al 1994;Peretti et al 2006;Husum et al 2008;Wnuk et al 2011;Wo´jcik et al 2011), and differences in the numbers of SCEs between old and young chinchillas were also observed in the present study. We observed a highly interesting interrelationship.…”
Section: Discussionsupporting
confidence: 79%
“…Age significantly affects the incidence of SCE. Older animals develop more SCEs per cell compared with younger animals (Sinha et al 1985;Lazutka et al 1994;Peretti et al 2006;Husum et al 2008;Wnuk et al 2011;Wo´jcik et al 2011), and differences in the numbers of SCEs between old and young chinchillas were also observed in the present study. We observed a highly interesting interrelationship.…”
Section: Discussionsupporting
confidence: 79%
“…In the older animals the frequency of SCEs was much higher. Such correlation was also observed in humans (Sinha et al 1985, Lazutka et al 1994, Husum et al 1986. Our own studies revealed that the age was a significant factor affecting the number of SCEs.…”
Section: Discussionsupporting
confidence: 73%
“…SCE incidence is affected by the age of animals. Older animals tend to have increasingly more SCEs (SINHA et al 1985;LAZUTKA et al 1994;PERETTI et al 2006;HUSUM et al 2008). Our study confirmed this regularity.…”
Section: Discussionmentioning
confidence: 99%